Creative and Strategic Capabilities of Generative AI: Evidence from Large-Scale Experiments - Noah Bohren; Rustamdjan Hakimov; Rafael Lalive (Institute of Labor Economics (IZA), 2024)
Generative artificial intelligence (AI) has made substantial progress, but its full capabilities remain unclear, and we still lack a comprehensive understanding of how people augment productivity with AI and perceive AI-generated outputs. This study compares the ability of AI to a representative population of US adults in creative and strategic tasks. The creative ideas produced by AI chatbots are rated more creative than those created by humans. Moreover, ChatGPT is substantially more creative than humans, while Bard lags behind. Augmenting humans with AI improves human creativity, albeit not as much as ideas created by ChatGPT alone. Competition from AI does not significantly reduce the creativity of men, but it decreases the creativity of women. Humans who rate the text cannot discriminate well between ideas created by AI or other humans but assign lower scores to the responses they believe to be AI-generated. As for strategic capabilities, while ChatGPT shows a clear ability to adjust its moves in a strategic game to the play of the opponent, humans are, on average, more successful in this adaptation.
Keywords: I24; J24; D91; C90; 330; creativity; ChatGPT; artificial intelligence; strategic skill; experiment; algorithm-aversion